2016
DOI: 10.1177/0956462415624058
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year trends of syphilis in sero-surveillance of pregnant women in Rwanda and correlates of syphilis-HIV co-infection

Abstract: Syphilis can be transmitted by pregnant women to their children and is a public health problem in Africa. A cross-sectional survey was conducted in 24 antenatal clinics from 2002 to 2003 and increased to 30 sites from 2005 to 2011. Participants were tested for syphilis and HIV. Multi-variate logistic regression was performed to identify risks associated with syphilis and its co-infection with HIV. Results showed that syphilis decreased from 3.8% in 2002 to 2.0% in 2011. Syphilis in the HIV-infected participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 11 publications
7
18
1
3
Order By: Relevance
“…It was previously reported that 215000 infants are at increased risk of dying from prematurity, low-birth-weight or congenital disease due to HIV/Syphilis co-infection in pregnant women especially in low-income countries [8]. Given the consequences of HIV/Syphilis co-infection in pregnant women in addition to being high-risk group [9,10], the continued surveillance of this co-infection is of paramount to establish the status of the diseases and increase the awareness.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that 215000 infants are at increased risk of dying from prematurity, low-birth-weight or congenital disease due to HIV/Syphilis co-infection in pregnant women especially in low-income countries [8]. Given the consequences of HIV/Syphilis co-infection in pregnant women in addition to being high-risk group [9,10], the continued surveillance of this co-infection is of paramount to establish the status of the diseases and increase the awareness.…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend of epidemics was found in Asia; the prevalence of syphilis was found at 1.6% in HIV infected women in India [21], at 3.6% in a female sex worker in Karnataka, India [22]. Even though the observed prevalence of syphilis in HIVpositive pregnant women was much lower than those reported by Sub-Sahara countries such as Rwanda, Tanzania, Ethiopia, Uganda and Zambia [13][14] [27] [28], extra attention should be given to those are experiencing HIV-syphilis co-infection, as it was associated with poorer maternal outcomes and higher risk of MTCT of both HIV and Syphilis [34] [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, without any interventions from gestation, infants who infected congenitally will grow up with pathogens, especially HBV and HIV [3] [4] [9], and transmit those to others at some stage of their lives. Infection of HIV and syphilis in infants often occur simultaneously due to the similar pathways of transmission (i.e., from the placenta) [10] [11] [12] [13] [14] [15]. Maternal co-infection with HIV and syphilis is dangerous.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations